2006
DOI: 10.1055/s-2006-944731
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic necrosectomy as primary therapy in the management of infected pancreatic necrosis

Abstract: Endoscopic necrosectomy is a safe method for treatment of infected pancreatic necrosis. Multiple procedures are usually needed. It may be combined with other methods of surgical intervention. Larger prospective studies will more precisely define its role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
122
0
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(128 citation statements)
references
References 10 publications
2
122
0
4
Order By: Relevance
“…In such cases with the application of drainage early operation can be avoided [1, 4,6,8,10,11,12,21,26,32,35,39,42]. Others suggest transluminal endoscopic (NOTES) procedure if percuteanous drainage is failed [7,13,15,27,30,31,41] Some authors suggest the combination of external and internal drainage with endoscpopic necrosectomy [27,30,]. Complications related to percutaneous drainage are rare.…”
Section: How To Drain?mentioning
confidence: 99%
See 2 more Smart Citations
“…In such cases with the application of drainage early operation can be avoided [1, 4,6,8,10,11,12,21,26,32,35,39,42]. Others suggest transluminal endoscopic (NOTES) procedure if percuteanous drainage is failed [7,13,15,27,30,31,41] Some authors suggest the combination of external and internal drainage with endoscpopic necrosectomy [27,30,]. Complications related to percutaneous drainage are rare.…”
Section: How To Drain?mentioning
confidence: 99%
“…In this chapter the authors suggest reviewing the transmural endoscopic (NOTES) necrosectomy as a minimal invasive method. More and more authors in selected patients use this method for necrosectomy with a successful rate of 73-92% [2,7,13,15,27,30,31,41]. The necrotic cavity can be drained to the stomach or the duodenum.…”
Section: How To Drain?mentioning
confidence: 99%
See 1 more Smart Citation
“…However, operation-related morbidity and mortality, and longer hospitalization are not uncommon complications [1,2] . Transgastric endoscopic necrosectomy has been recently introduced as the effective and alternative management for infected pancreatic necrosis and pancreatic abscess [3][4][5][6][7] . However, up to 40% of patients who undergo endoscopic necrosectomy may need an additional percutaneous approach for subsequent peripancreatic fluid collection or non-resolution of pancreatic necrosis [8] .…”
Section: Introductionmentioning
confidence: 99%
“…Similar success rates were reported subsequently in other small retrospective studies. [45][46][47] Subsequently, two large multicentre trials from Germany and USA confirmed a clinical success rate of over 80% and an acceptable rate of complication of 14% to 20% for endoscopic necrosectomy. 48,49 Biliary FC-SEMS provide a larger diameter fistulous tract for drainage of WOPN but will not permit the advancement of an endoscope into the collection.…”
mentioning
confidence: 99%